Physico-Chemical and Microbial Profile of Fresh Rabbit Meat - Swami, J.N.; Rindhe, S.N.; Shashikumar, M.; Raut, S.S.; Dange, Anil (Journal of Meat Science, 2022)
Present study was conducted to assess certain physico-chemical and microbial quality of rabbit meat sold at retail shops. Rabbit meat samples were collected in sterile LDPE; brought to laboratory for further evaluation.The pH of fresh rabbit meat was 5.60±0.01 and the TBARS value ranged between 0.11 to 0.24 with mean value of 0.18 ± 0.01mg malonaldehyde/ kg. The tyrosine values were ranged between 18.09 and 21.12 with mean value of 19.60 ± 0.42 mg/ kg. The Extract release volume value of fresh rabbit meat sample was 21.90 ± 0.15 ml. The standard plate count of fresh rabbit meat was in the range of 4.52 to 4.69 log cfu/gm with a mean value of 4.60 ± 0.02 log cfu/gm. E. coli count of fresh rabbit meat was observed to be between 2.10 and 2.18 log cfu/gm with an average of 2.14 ± 0.04 log cfu/gm. The moisture content of fresh rabbit meat samples varied from 71.50 to 72.83 % with mean value of 72.16 ± 0.42 %. The protein content of fresh rabbit meat ranged from 19.03 to 21.40 % with mean value of 20.21 ± 0.06 % while the fat content was found to be in the range of 6.40 to 6.63 % with an average of 6.50 ± 0.02 %.
Keywords: Rabbit meat; Physico-chemical; microbial quality